Kedudukan Seorang Istri Sebagai Ahli Waris yang Pernikahannya Didaftarkan setelah Suami Meninggal Dunia - Cynthia Phillo; Mella Ismelina FR (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study is to discuss that marriages that have not been registered when one of the partners is still alive, can be injured even though one of the partners has died. This research method uses normative legal methods. The results of this study indicate that the position of a wife as an heir whose marriage is registered after her husband dies in Law Number 1 of 1974 concerning Marriage requires every couple who enters into a marriage to register the marriage before the Marriage Registrar to become the administration of the marriage and provide legal certainty for those who enter into marriage in order to obtain legal protection for the fulfillment of the rights of wife and children. Then in the case of a couple who do not register their marriage, a wife is not entitled to be the heir of the wealth left by her husband when his husband died. In order to become an heir, a wife whose husband has died must first legalize her marriage by registering her marriage so that her marriage is considered valid in the eyes of the law.